2021
DOI: 10.1093/jisesa/ieab046
|View full text |Cite
|
Sign up to set email alerts
|

The Galleria mellonella-Enteropathogenic Escherichia coli Model System: Characterization of Pathogen Virulence and Insect Immune Responses

Abstract: The use of Galleria mellonella (Linnaeus) (Lepidoptera: Pyralidae), an economical insect model, for the study of enteropathogenic Escherichia coli (Migula) (EPEC), a diarrheagenic human pathogen, has been demonstrated previously but remains poorly understood. The present study characterizes the Galleria-EPEC system extensively for future studies using this system. We found that EPEC causes disease in G. mellonella larvae when injected intrahemocoelically but not orally. Disease manifests as increased mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…In addition to this, three more groups of 10 larvae were injected with non-pathogenic E. coli ATCC25922 to evaluate whether larvae were killed by non-infection related reactions, with 10 µL of PBS to measure any lethal effects due to physical injury and positive control inoculation with pathogenic strain KP-2 belonging to ST-131. Results were analyzed by Kaplan-Meier survival curves (GraphPad Prism statistics software) ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, three more groups of 10 larvae were injected with non-pathogenic E. coli ATCC25922 to evaluate whether larvae were killed by non-infection related reactions, with 10 µL of PBS to measure any lethal effects due to physical injury and positive control inoculation with pathogenic strain KP-2 belonging to ST-131. Results were analyzed by Kaplan-Meier survival curves (GraphPad Prism statistics software) ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to mention that G. mellonella in vivo model has been used to study E. coli pathogenicity. Based on this model, it is possible to evaluate the immune innate response of G. mellonella against bacteria, namely, melanization and antimicrobial peptides (AP) production (such as cecropin and gloverin) [ 45 ]. To achieve a more close experimental design to the porcine model, pig serum has been also studied, since it contains a variety of AP, inhibiting bacterial cell growth and constituting a host's innate immune system against bacterial infection [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pS88 plasmid conjugation strategy was based on the presence of the ColV-encoding cva operon on the pS88 plasmid of bovine AE-STEC and EPEC O80:H2 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The recipient strain was the E. coli K12 DH10B strain harboring the recombinant plasmid pAuto-ColV-Switch1.0 carrying a synthetic ColV-encoding locus (received from Syngulon Company, Seraing, Belgium; ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides their low cost and the possibility of testing multiple groups of larvae in a short time, G. mellonella larvae possess an innate immune system similar to mammals and can be maintained at 37 °C, like the bacterial pathogens of mammals [ 25 , 29 ]. So, it was recently observed that the STX2d phage and the type 3 secretion system (T3SS) contribute to the virulence of AE-STEC O80:H2 and EPEC O127:H6, respectively, in G. mellonella larvae [ 25 , 30 , 31 ], while the contribution of the T3SS to the virulence of AE-STEC O157:H7 is less clear [ 32 , 33 ]. However, no study has been performed yet to assess the role of the pS88 plasmids of AE-STEC and EPEC O80:H2.…”
Section: Introductionmentioning
confidence: 99%